One-man Below-knee Analgesia in the Emergency Department with Minimal Equipment Using the Single-operAtor Nerve block under Direct ultrasound visualization in emergencY (‘SANDY’) Technique: A Retrospective Analysis - Sandeep Nathanael David; Pradeep Daniel Katumalla; Priya Ganesan; Paul Prabhakar Abhilash Kundavaram (Eurasian Journal of Emergency Medicine, 2023)

(untitled)
Aim:To demonstrate the efficacy of single-person bedside ultrasound guided (USG) Popliteal-Sciatic Nerve Block (PSNB) using minimal equipment in the emergency department (ED) for managing below-knee trauma.Materials and Methods:This single-centre retrospective analysis was done at the ED of a tertiary care centre in Southern India from 01/12/2021 to 31/06/2022. The charts of all adult patients who received the block were reviewed and the reduction in pain score after the block, block success rate, and incidence of side effects were analyzed.Results:One hundred and three patient records were reviewed during the study period. Ninety-eight males (95.1%) and 5 females (4.9%) had received the block. 87.4% of the patients were road accident victims. The block was given by a single operator under ultrasound guidance with the stylet of an 18 gauge intravenous cannula mounted on a syringe filled with 1% lidocaine. The mean pain score before and 10 minutes after administering the block was 8.85 [standard deviation (SD) ±0.78] and 2.06 (SD ±1.75) respectively. The block success rate was found to be 93.2%. Except for 7 failed blocks, there were no adverse events following the procedure.Conclusion:USG PSNB is a safe, consistent, and relatively long-lasting anesthetic technique in the management of below-knee trauma in the ED.